(untitled) (Archives of Pediatrics of Uruguay, 2022)
Introduction: in January 2020, a new coronavirus was identified as the etiology of a severe acute respiratory syndrome, which was called coronavirus 2 (SARS-CoV-2). The associated illness is known as coronavirus disease 2019 (COVID-19). SARS-CoV-2 spread rapidly worldwide, becoming a pandemic in March 2020. The pediatric population involved 1-2% of the total confirmed cases, with a mortality rate of less than 0.2%. In line with the global trend, children under 19 years of age showed a much lower number of hospital admissions for COVID-19 in Uruguay compared to the remaining age groups, as well as lower number of ICU admissions and deaths. The objective of this paper is to describe pediatric admissions with SARS-Cov-2 infection at a private health provider in Montevideo city. Methodology: we included all patients under 15 years of age with a diagnosis of viral infection by Covid-19 who required hospitalization in moderate care, between 04/20 and 02/22. We used polymerase chain reaction and antigen detection for Covid-19 for the diagnosis of acute infections and serology tests for the diagnosis of a previous infection. Results: of the 1,164 patients admitted in that period, 2% were diagnosed with Covid 19 infection. 80% had an epidemiological link, 69% had home infections. 8% under 1 year of age, 69% between 1-11, 23% over 11 years of age. 27% had comorbidities: asthma and encephalopathy, 57% of them had concomitant thorax pathologies. The most frequent reasons for admission were respiratory symptoms, with fever and skin lesions, surgical pathologies, and neurological symptoms. 2 required ICU admission. No deaths were reported. The median number hospitalization days was 4 days (1-18 days). Conclusions: although the percentage of children admitted with SARS-CoV-2 infections was low, the clinical manifestation was varied, most presented mild respiratory infections. Patients with comorbidities were more likely to develop moderate to severe acute illness. The probability of SARS-CoV-2 infection should be taken into account when other symptoms appear during the course of viral infections.